Thirty people are eligible to win cash prizes. The number of each cash award prize is shown in the table. Prizes will be given out randomly one at a time. What is the probability of the first person winning the $50 prize?
Answer:
0.1667
Step-by-step explanation:
Given that the Total number of people who are eligible to win cash prizes is 30.From the given table we notice that 5 people win $50 cash prize.
The probability of the first person winning the $50 prize is therefore :
Hence the probability of the first person winning the $50 prize is 0.1667
Answer:5
Step-by-step explanation:there are 6 boxes between the top of the 3rd box and the bottom of the 10th box.
Since each box is 10 inches tall, the length of the 6 boxes sum up to 60 inches.
and since 12 inches =1 feet,
Then 60 inches = 5 feet
How to solve
Let "y" = the unknown number of feet's
12 inches = 1 feet
60 inches = y
Cross multiply
> 12×y =60×1
> 12y =60
Divide both sides by 12 since you want the value of "y".
> 12y÷12=60÷12
So 12 cancels out leaving the final answer to be:
> y=5
Answer:
Step-by-step explanation:
We just have to count how many boxes is between the top of the third one and the bottom of the tenth box, then we transform from inches to feet.
So, the problem says "from the top of the third box" this means that the inches that matters is form the fourth box. "the bottom of the tenth box" means that it's until the ninth box. In total, there are 6 boxes. If each box is 10 inches high, the total distance would be 6(10 inches) = 60 inches.
Now we have the total distance, we transform it to feet. We know that one feet is 12 inches, using the rule of three we have:
60 inches are equivalent to 5 feet.
Therefore, there are 5 feet between the top of the third box and the bottom of the tenth box.
Answer:
315
Step-by-step explanation:
42÷2 = 21
2×21 = 42
So, 15×21 = 315
315÷21 = 15
Answer:
315
Step-by-step explanation:
42÷2 = 21
2×21 = 42
So, 15×21 = 315
315÷21 = 15
B)-2
C)15
D)40
Answer:
(c) For p = 15, leaves a remainder of -2 when divided by (x-3).
Step-by-step explanation:
Here, The dividend expression is = E(x)
The Divisor = (x-3)
Remainder = -2
Now, by REMAINDER THEOREM:
Dividend = (Divisor x Quotient) + Remainder
If ( x -3 ) divides the given polynomial with a remainder -2.
⇒ x = 3 is a solution of given polynomial E(x) - (-2) =
= S(x)
Now, S(3) = 0
⇒
or, p =1 5
Hence, for p = 15, leaves a remainder of -2 when divided by (x-3).